A conceptual review on critical reading literacy on the 21st century - Muzaki, Ferril Irham (Common Ground's Interdisciplinary Social Sciences Research Network, 2023)
Literacy knowledge means the capability to read and write, understand information and express concrete and abstract ideas. The undetermined supposition is that" read and write" means reading and writing textbook. Although media and computer knowledge are occasionally mentioned in this description, media knowledge is frequently defined as the capability to understand how TV and flicks manipulate cult, and computer knowledge is generally defined as the capability to use computers to perform colorful tasks, similar as access the web. knowledge has been an issue on numerous people's minds recently. It's one of those subjects that all lay people believe to be experts in. still, when introducing ignorance measures or developing programs, it becomes clear that we know much lower than we suppose. It's kind of comforting to know that experts have their differences too.